SENGKETA KEPEGAWAIAN PERSPEKTIF SIYASAH SYAR’IYYAH: Analisis Putusan PTUN Makassar Nomor: 64/G/2020/Ptun.Mks - Wahyuni, Masra; Tenripadang, Andi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
Personnel disputes arise from the issuance of a State Administrative Decree in the field of personnel by the State Administrative Agency or Official regarding the position, obligations, rights, and guidance of the State Civil Apparatus. This type of research is classified as qualitative field with normative juridical and syar'i approaches. The results showed that based on legal considerations in Decision PTUN Makassar Number 64/G/2020/PTUN. Mks, the judge considered that the Mayor of Makassar had committed an act that was not in accordance with the procedure and that the action violated the principles of Good Government, especially the principle of legal certainty, the principle of not abusing authority and the principle of accuracy. The concept of siyasah syar'iyyah, also known as the principle of justice and non-discrimination, wants every leader to be fair and not discriminate in making policies. So that the actions of the Mayor of Makassar can also be interpreted as having violated these two principles.